2011
DOI: 10.1002/jnr.22743
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptors regulate cholesterol homeostasis in oligodendrocytes

Abstract: Cholesterol synthesis and transport in oligodendrocytes are essential for optimal myelination and remyelination in pathological conditions such as multiple sclerosis. However, little is known about cholesterol homeostasis in the myelin-forming oligodendrocytes. Liver X receptors (LXRs) are nuclear oxysterol receptors that regulate genes involved in cholesterol homeostasis and may therefore play an important role in de- and remyelination. We investigated whether LXRs regulate cholesterol homeostasis in oligoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 61 publications
(75 reference statements)
4
49
0
Order By: Relevance
“…We describe for the first time that Idol is involved in the regulation of lipid uptake in oligodendroglial cells. This finding is consistent with a recent report showing that liver X receptors (LXRs) that are transcriptional regulators of Idol expression control lipid metabolism in this cell type (Nelissen et al, 2012).…”
Section: Ndrg1 and Cmt4dsupporting
confidence: 93%
“…We describe for the first time that Idol is involved in the regulation of lipid uptake in oligodendroglial cells. This finding is consistent with a recent report showing that liver X receptors (LXRs) that are transcriptional regulators of Idol expression control lipid metabolism in this cell type (Nelissen et al, 2012).…”
Section: Ndrg1 and Cmt4dsupporting
confidence: 93%
“…We demonstrated both in vitro and ex vivo that LXR activation stimulates morphological cell maturation of oligodendroglial cells. Interestingly, Hendriks' group showed that a 72-h treatment with TO9 of late immature rat oligodendrocytes reduced cell branching (23). These data and ours suggest that LXR activation exerts a differential effect regarding the differentiation status of oligodendrocytes.…”
Section: Discussionsupporting
confidence: 77%
“…For instance, Apolipoproteins (APOD and APOE) were upregulated in both proximal and distal stumps of nerves treated with rapamycin + NGF, as well as in the distal stump of nerve treated only with NGF. These proteins increase axonal regeneration in PNS, and regulate oligodendrocyte differentiation and myelination in CNS, as well as protect neurons from apoptosis [102][103][104]. Serotransferrin (TF), which increases remyelination [105,106], was upregulated in both the proximal and distal stumps of nerves treated with rapamycin + NGF.…”
Section: Resultsmentioning
confidence: 99%